Katekese Orang Muda Katolik: Bersiaplah Menghadapi Perubahan - Mikaela Mikaela; Sisilia Santi Dey; Sebastianus Aldo; Sefrinanda Ida Sarida Ulan; Kesin Kesin; Willyam Roni; Victoria Dewi Anggreyani Song; Lidwina Prada L; Margaretha Hong Lung; Helena Trevirini; Gunawan Gunawan; Thomas Jiu; Elsonsius Gade (Literasi Nusantara Publisher, 2023)
This Community Service activity aims to deepen the faith of young people, help them understand Church teachings, and increase their knowledge in preparing themselves for future changes. Partners in this PkM are the Catholic Youth of St. Paulus Kedang Ipil Station. The changing and developing world situation calls on young people to adapt themselves to pastoral care and improve their ministry. In 2022, the Samarinda Archdiocese has set a pastoral focus, one of which is preparing to welcome the blessings as well as the consequences of the presence of the National Capital in East Kalimantan Province. The approach that will be used to achieve the goals of community service activities is a catechism. The result of this activity is that catechesis for young Catholics is carried out for the sake of developing the faith of young people because faith development lasts a lifetime, so catechism is also needed which is also permanent. Catechesis is like sharing experiences of faith, not only sharing but also mutually enriching and developing faith and knowledge.